2017
DOI: 10.4172/2157-7110.1000706
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Soft White Cheese Produced Traditionally in Jordan

Abstract: To determine the hygiene and processing aspects and the microbiological quality of soft white cheese produced traditionally in Jordan, 30 samples were collected from dairy workshops and plants in major Governorates of Jordan. A questionnaire was filled by interviewing each producer about the quality, Food hygiene and safety aspects of production prevailing during processing were also investigated.The averages of log 10 of the standard plate count (SPC), and the counts of lactic acid bacteria count (LABC), Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…S. aureus and yeasts and moulds counts were significantly (P<0.001) affected by heat treatment of cheese milk being high in T1 cheese (log10 1.88 cfu/gm, and log10 5.53 cfu/gm, respectively), while TVB and E. coli counts were not, although the slightly high count of TVB was in T1 (log10 6.64 cfu/gm), and E. coli count was log10 <1.0 cfu/gm for T1 and T2. The high microbial content of soft white cheese reflects the poor hygienic conditions during cheese production, lack of cooling and heat treatment, while the contamination of cheese with S. aureus suggests inadequate care during processing, and such foods certainly pose a danger to consumers [34]. This result is in agreement with Johnson et al [35] who found that the heat treatment at 68 °C significantly reduced S. aureus count.…”
Section: Effect Of Heat Treatment Of Milk On the Microbiological Characteristics Of White Cheesesupporting
confidence: 84%
“…S. aureus and yeasts and moulds counts were significantly (P<0.001) affected by heat treatment of cheese milk being high in T1 cheese (log10 1.88 cfu/gm, and log10 5.53 cfu/gm, respectively), while TVB and E. coli counts were not, although the slightly high count of TVB was in T1 (log10 6.64 cfu/gm), and E. coli count was log10 <1.0 cfu/gm for T1 and T2. The high microbial content of soft white cheese reflects the poor hygienic conditions during cheese production, lack of cooling and heat treatment, while the contamination of cheese with S. aureus suggests inadequate care during processing, and such foods certainly pose a danger to consumers [34]. This result is in agreement with Johnson et al [35] who found that the heat treatment at 68 °C significantly reduced S. aureus count.…”
Section: Effect Of Heat Treatment Of Milk On the Microbiological Characteristics Of White Cheesesupporting
confidence: 84%
“…Different extracts were added to these ditches (100µl) and plates were incubated then at 37°C. for bacteria and at 35°C for 48 hrs for fungi After 24 hrs diameter of clear zone produced surrounding the ditches were measured to the nearest mm with the help of scale and were presented in the graph [18], [19] [21], [22] Cheese Processing and Adding Plant Extract…”
Section: Turbid Metric Methodsmentioning
confidence: 99%
“…The average total bacteria count ranged from 4.881 to 6.835 log cfu/g, while the total yeast/molds ranged from 1.727 to 4.795 log cfu/g. In another study, the average total bacterial count in fresh white cheese was log 10 7.7 cfu/g (Haddad and Yamani, 2017). The combination of cinnamon and lemongrass powder (T4) had the highest total bacteria count, while the combination of lemongrass and turmeric powder (T6) had the highest total yeast/molds count.…”
Section: Microbiological Qualitymentioning
confidence: 96%